Leak Detection in Gas Pipeline using Hilbert-Huang Transform - N. F., Adnan; M. F., Ghazali; Makeen, Mohd Amin; A. M. A., Hamat (Trans Tech Publications, 2015)
This paper proposes a leak detection method using acoustic. The Hamming chirp signal injected into the pipeline system and the estimation of the leak location from the delay time passing by the reflection in the pipeline if there is a leak. By using Hilbert-Huang Transform (HHT), it can give a useful signal to verify the leak. HHT transforms Empirical Mode Decomposition (EMD)and Hilbert Spectrum analysis to perform time-frequency analysis. The leak location can be detected by multiplying by the speed of sound. This simple method gives accurate leak location and easy to implement.